The effect of potassium fertilization on the inner values of spice pepper - Irinyi, B.; Kapitány, J.; Terbe, I. (International Journal of Horticultural Science, 2006)
To reserve the fertility of soil is the basic condition of successful cultivation. The field specific nutrient supply, based on soil tests is very important in both economy and ecology aspects. Spice pepper plants have high nutrient demands. Proper nutrient supply has importance not only from the point of potential yield levels, but make a major contribution to quality. This is the reason which necessitates the rational development of nutrient supply as an the elements of the production technology. Our objective was to offer a contribution to this job through our nutrient trials. Experiments on the nutrient supply of spice pepper were set up in the 2005 growing season in order to decide whether yields and fruit composition parameters of pepper could be increased by means of increased K fertiliser closes with lower N:K ratios. Several forms of potassium were used, as well as applying microelement top dressings in the single treatments. It was found that higher K doses lead to increased yields, and the influence on dry matter and pigment content proved beneficial too. Potassium applied in the form of patentkali seemed to be better than in that of potassium-sulphate.